The enhancement mechanism of dielectric properties of Pb(Zr, Ti)O3 via (Mg2+, Sb3+) incorporation for supercapacitors. (December 2020) - Craciun, F.; Dimitriu, E.; Vasile, B.S.; Negrila, C.C.; Trusca, R.; Birjega, R.; Cernea, M.
Abstract: Due to the extraordinary versatility of the perovskite structure in accommodating different dopant ions in its structure, in recent years a huge number of multifunctional perovskite materials have been developed. In this work we aim to obtain high temperature-stable and huge dielectric constant materials for supercapacitors by doping divalent Mg 2+ and trivalent Sb 3+ ions into the octahedral sites, and divalent Sr 2+ ions into the dodecahedral sites of lead zirconate-titanate perovskite. The resulting (Pb0.95 Sr0.05 )(Zr0.425 Ti0.45 Mg0.042 Sb0.083 )O3-δ is examined by X-ray diffraction, energy-dispersive X-ray spectroscopy, X-ray photoelectron spectroscopy (XPS), high resolution transmission electron microscopy (HRTEM), dielectric spectroscopy (DS) and resonance dielectric spectroscopy (RDS) in order to correlate composition, local structure, ion valence and chemical environment of the doped material with the dielectric properties. HRTEM evidences that a composite structure, with co-existent ferroelectric domains and relaxor nanodomains, is formed by doping. XPS shows that Sb 3+ and Mg 2+ substitute for the Ti 4+ /Zr 4+ ions, pointing to these strong defects as the main cause for the appearance of the relaxor phase. DS and RDS found that the ferroelectric lead zirconate-titanate transforms into a re-entrant relaxor-ferroelectric composite with a huge dielectric constant of about 10 4 which remains stable (within ±10%) in the high temperature range up to 250 °C, pointing to this mechanism of relaxor phase re-entrance below the normal ferroelectric phase transition, as being responsible for the enhancement. Graphical abstract: Image 1 Highlights: High temperature-stable and huge dielectric constant materials are obtained by doping (Mg 2+, Sb 3+ ) in lead zirconate-titanate. HRTEM evidenced a composite structure, with co-existent ferroelectric domains and relaxor nanodomains. XPS showed that Sb 3+ and Mg 2+ substitute for the Ti 4+ /Zr 4+ ions. Dielectric spectroscopy showed that the ferroelectric transforms into a re-entrant relaxor-ferroelectric composite. A huge dielectric constant (∼10, 000) which is stable (within ±10%) in the high temperature range up to 250 °C, is obtained.